Evaluación económica de materiales forrajeros en Colombia - Enciso, Karen; Burkart, Stefan (International Center for Tropical Agriculture, 2019)
This document aims to assess the financial viability of two new forage options to be released in Colombia, as a result of different evaluation and selection processes conducted by AGROSAVIA and its partners. The following varieties were evaluated from an economic perspective: (i) Brachiaria brizantha 26124 hp. Orinoquia for meat production in the Colombian East Plains region; and ii) Megathyrsus Maximus cv. Savannah agrosavia for meat production in the Colombian humid Caribbean region. The methodology is based on a discounted free cash flow model, the estimation of financial feasibility indicators, and an analysis that is based on Monte Carlo simulation, to consider the risk level of critical variables of the model.